(untitled) (Research, Society and Development, 2022)
Introduction: The immunization of children is a necessary method for reducing infant mortality rates and for the development of immune capacity; however, it is often not prioritized by parents and guardians. A situational diagnosis using data contained in the Information System of the National Immunization Program (SI-PNI), showed low adherence to vaccination. Therefore, the project aimed to update the vaccination schedule for children in the Manoel Dias Branco neighborhood, located in Fortaleza, Ceará, through an action to encourage vaccination. Methodology: this is action research conducted by medical students from a private university in Fortaleza, in partnership with UAPS Rigoberto Romero between March and May 2022, with children aged 0 to 12 years registered in the UAPS. Results and Discussion: there was a high demand for immunobiologicals, showing that actions by the entire team are important for the promotion of health education, since learning about immunobiologicals allows the co-responsibility of the community, generating a significant impact. Conclusion: through this experience the relevance of developing actions to encourage immunization is evident. Therefore, having evidenced the increased demand for vaccines in the post-pandemic period, acting in vaccination campaigns is of great importance to the population, being necessary for the promotion of these interventions with a greater frequency in the community.